2017
DOI: 10.1111/cbdd.12926
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐based approaches for the design of benzimidazole‐2‐carbamate derivatives as tubulin polymerization inhibitors

Abstract: Microtubules are highly dynamic assemblies of α/β-tubulin heterodimers whose polymerization inhibition is among one of the most successful approaches for anticancer drug development. Overexpression of the class I (βI) and class III (βIII) β-tubulin isotypes in breast and lung cancers and the highly expressed class VI (βVI) β-tubulin isotype in normal blood cells have increased the interest for designing specific tubulin-binding anticancer therapies. To this end, we employed our previously proposed model of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
1
12
0
1
Order By: Relevance
“…The quinazoline derivative formed three key H‐bonds in the NZ site with E198 side chain and V236 main chain. Interestingly, the interaction profile of 4 i in the NZ site is consistent with the previously proposed pharmacophore hypotesis . On the other hand, the acetamide group places the quinoline substituent at the COL site, where the chlorine group could form a H‐bond with the N256 side chain.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The quinazoline derivative formed three key H‐bonds in the NZ site with E198 side chain and V236 main chain. Interestingly, the interaction profile of 4 i in the NZ site is consistent with the previously proposed pharmacophore hypotesis . On the other hand, the acetamide group places the quinoline substituent at the COL site, where the chlorine group could form a H‐bond with the N256 side chain.…”
Section: Resultssupporting
confidence: 87%
“…According to our previous pharmacophore hypothesis and the recent crystallographic data, the following pharmacophoric features should be addressed by a molecule to bind in the NZ site: an aromatic scaffold, an H‐bond acceptor, two nearby H‐bond donors, and a distal aromatic substituent (Figure B) . The protonated state of E198 residue favors the H‐bond interaction with the scaffold fused nitrogen, while the H‐bond donor groups interact with either E198 or Y200 side chains and with the main chain carbonyl of V236 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous computational studies, our group assessed the importance of key NZ binding site residues in the interaction and affinity of benzimidazole derivatives to different parasite and mammalian β‐tubulins . Those studies, along with experimental information, indicated that NZ and other derivatives interaction with E198 is responsible for its binding, and that substitutions or mutations at positions 165, 167, 200 or 239 exhibit minor alterations to the NZ affinity to the β subunit . Moreover, we suggested that the NZ‐1,6 tautomer might modify its interaction with E198 to interact with the main‐chain carbonyl group of V236.…”
Section: Figurementioning
confidence: 99%
“…6 Studies have suggested that benzimidazole anthelmintic drugs inhibit microtubule dynamics by promoting microtubule depolymerization. [7][8][9][10] Because microtubules play a crucial role in mitosis, cell division, cell structure maintenance, and many other cellular events, reagents that disrupt microtubule dynamics can potentially serve as anticancer agents. [11][12][13][14][15] Although there are numerous publications regarding the anticancer activity and mechanism of action of benzimidazole anthelmintic drugs, there is no conclusive report on the anticancer profile.…”
Section: Introductionmentioning
confidence: 99%